Pharmacological targeting of brain inflammation in epilepsy: Therapeutic perspectives from experimental and clinical studies. (16th July 2018) - Ravizza, Teresa; Vezzani, Annamaria
Summary: Increasing evidence supports a pathogenic role of unabated neuroinflammation in various central nervous system (CNS) diseases, including epilepsy. Neuroinflammation is not a bystander phenomenon of the diseased brain tissue, but it may contribute to neuronal hyperexcitability underlying seizure generation, cell loss, and neurologic comorbidities. Several molecules, which constitute the inflammatory milieu in the epileptogenic area, activate signaling pathways in neurons and glia resulting in pathologic modifications of cell function, which ultimately lead to alterations in synaptic transmission and plasticity. Herein we report the up‐to‐date experimental and clinical evidence that supports the neuromodulatory role of inflammatory mediators, their related signaling pathways, and involvement in epilepsy. We discuss how these mechanisms can be harnessed to discover and validate targets for novel therapeutics, which may prevent or control pharmacoresistant epilepsies.